PENGARUH NET INTEREST MARGIN (NIM) TERHADAP PERUBAHAN LABA PADA BPD DI INDONESIA DENGAN NON PERFORMING LOAN (NPL) SEBAGAI VARIABEL MODERATING - Astohar, Astohar (Sekolah Tinggi Ilmu Ekonomi Totalwin, 2014)
Bank has a role in economic development as a mediation betweenthe parties requires that the excess funds to fund or otherwise. As bothparties are intermediaries profit into the banking purposes. Earningschanges of concern to determine future business prospects of the regionaldevelopment banks. This study aimed to analyze the influence of the NetInterest Margin (NIM) to changes in earnings with Non-PerformingLoan (NPL) as a moderating variable.The study was conducted atRegional Development Bank in Indonesia, Bank Indonesia registered inthe period 2006-2011 by taking a sample of 26 banks. Data collectionmethods used are literature and documentation. Analysis using datanormality test, deviation classical assumptions, test the moderatingregression analysis, and hypothesis testing using SPSS tool.The resultsshowed the Net Interest Margin (NIM)) proved to have a positive andsignificant effect on earnings changes. While non-performing loan (NPL)is not proved to be the variable that strengthens the influence of the NetInterest Margin (NIM)) to changes in earnings.